Activation and regulation of IL-1β in dengue virus - Nafisah Zakariah (2011)
Dengue virus can elicit a spectrum of clinical manifestations from the mild dengue fever to severe dengue haemorrhagic fever and septic shock. To date, no effective vaccines exist. A hallmark characteristic of DENV is plasma leakage and liver damage. Elevated inflammatory response by our innate immune system through excessive proinflammatory cytokine release is often implicated in the pathogenesis of DENV. DENV-2, was shown to infect a variety of human cell lines. Its induction of caspase-1, generally responsible for activation of IL-1 proinflammatory IL-1β and IL-18 into its mature products, was studied to understand the impact on severity and viral replication. Both cytokines, especially IL-1β, were upregulated with correlation to caspase-1 activation in U937 and HUH-7, indicating major roles of macrophages and liver in diseases severity and pathology. However, H1299 p53-deficient cell line showed otherwise implying that these cytokines caspase-1 pertinent role in inflammatory response. Decrease in cytokine levels at later stage of infection triggered possibility of cell death being the result of virus induced, p53-mediated, caspase-1 dependent apoptosis. Together, activation and regulation of IL-1β plays an essential, cell-specific, role in the innate inflammatory response to DENV infection. Hopefully, understanding the progression of disease severity would pave progress towards vaccine development.